سلطة الحلول وتطبيقاتها على هيئات البلدية - كشحة, محمد الصالح (جامعة الوادي University of Eloued, 2017)
الحلول هو سلطة استثنائية مخولة للجهات الوصية للقيام وتنفيذ بعض الالتزامات بدلًا من الهيئات اللامركزية نتيجة عدم قيام هذه الأخيرة بذلك عن امتناع أو إهمال أو عجز رغم تنبيهها بذلك ويعتبر أخطر أنواع الرقابة الممارسة عن الهيئات اللامركزية بسبب القيام بهذه الإعمال بدلًا منها وتتحمل هذه الأخيرة مسؤولية ذلك، ورغم أن المشرع قد قيد الحال بمجموعة من الضوابط كضرورة وجود نص قانوني يجيز استخدام هذه السلطة إلا أنه يبقى كقيد على البلديات حيث تظهر سلطة حلول الوالي محل هيئة المداولة في حالة التصويت على ميزانية البلدية بدون توازن، وعند عملية تنفيذ الميزانية التي يتولاها رئيس المجلس الشعبي البلدي، وعندما لا يصوت على ميزانية البلدية بسبب اختلال داخل المجلس الشعبي البلدي، أما الحلول محل الهيئة التنفيذية فيظهر في مجال الضبط الإداري وكذلك فيما يتعلق بأرشيف البلدية، وعندما يمتنع رئيس المجلس الشعبي البلدي عن اتخاذ القرارات الموكلة له بمقتضى القوانين والتنظيمات وكذلك في حالة رفض رئيس المجلس الشعبي البلدي إصدار نفقة إجبارية. Abstract: Solutions are an exceptional authority that is vested in the authorities to carry out and implement certain obligations instead of decentralized bodies as a result of the failure of latter to refrain from negligence or deficit, despite being alerted. In spite of , the fact that legislator has restricted the case with a series of controls such as the need for legal text that permits the use of this authority, it remains a restriction on the municipalities, where the power of governor's solutions shows the deliberative authority in the case of voting on municipal budget without balance. And when he does not vote on the budget of the municipality due to an imbalance within Municipal People's Assembly. The solutions of the executive branch appear in the area of administrative control as well as with regard to the municipal archives, and when the President of the People's Assembly of the Council takes the decisions entrusted to him under the laws as well as in the case of the President of the People's Council of the People's Assembly to issue compulsory maintenance.
Keywords: الحلول؛ البلدية؛ جهة الوصاية؛ المجلس الشعبي البلدي